(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“Poverty is the worst form of violence “Poverty is a national issue that is becoming progressively worse, as the society progresses into the future. The impoverished fall victim to poor health conditions, education and exploitation. This disease spreading at an alarming rate affecting too many human beings with no cure in sight.It was sickening to read the newspaper article of Hindustan Times dated 26th October 2015, titled “They are living on the edge”, which stated the pathetic conditions and the vulnerability of the children of the poor working parents in the slums due to lack of proper and safe infrastructure facilities for child care.Such news evokes emotions and sensations about doing something that deals with human aspects. As an architect, this information led to this thesis topic which is intended to fight the battle on poverty and related problems and get to the humanitarian, social responsibility to serve the human, every human.